PENGARUH LAMA PENYIMPANAN INANG PADA SUHU RENDAH TERHADAP PREFERENSI SERTA KESESUAIAN INANG BAGI Trichogrammatoidea armigera NAGARAJA - Husni Husni; Alfian Rusdy; Pudjianto Pudjianto; Zulfanazli Zulfanazli (Jurnal Floratek, 2010)
The purpose of this study was to investigate effect of storage period length under low temperature on host preference and host suitability for egg parasitoid, Trichogrammatoidea armigera.  In this study, Corcyra cephalonica eggs were used as the alternative host.  The result showed that the storage of host eggs under low temperature for 1.5 to 3 hours was able to delay host egg hatching until the day 5, however, for normal host eggs the hatching time was started at day 4.  This method did not exert a negative effect on host preference and host suitability for parasitoid T. armigera.  The rate of parasitism on the stored hosts was more than 90%, and it was not significantly different from the normal host.  T. armigera progeny (offspring) emerged from the stored host was also very high (more than 100%).  The result also showed that the percentage of T. armigera female progeny emerged from stored hosts higher than the normal host.  The female progeny emerged from normal host was 51%, while from hosts stored under low temperature for 1.5, 2.0, 2.5 and 3 hours were 69,49%, 66,03%, 66,16% and 71,10%, respectively.  The results indicated that the stored host eggs under low temperature (1– 4 oC) for 1,5 – 3,0 hours did not kill the host embryo, but only delay the hatching times.  Therefore, the availability of a sufficient number of fresh hosts could be maintained in the laboratory, so that the efficiency of mass rearing program of T. armigera parasitoid could be increased.